2024
DOI: 10.3390/bioengineering11040308
|View full text |Cite
|
Sign up to set email alerts
|

Design, Manufacture, and Characterization of a Critical-Sized Gradient Porosity Dual-Material Tibial Defect Scaffold

Ming-Chan Lee,
Cheng-Tang Pan,
Wen-Fan Chen
et al.

Abstract: This study proposed a composite tibia defect scaffold with radial gradient porosity, utilizing finite element analysis to assess stress in the tibial region with significant critical-sized defects. Simulations for scaffolds with different porosities were conducted, designing an optimal tibia defect scaffold with radial gradient porosity for repairing and replacing critical bone defects. Radial gradient porosity scaffolds resulted in a more uniform stress distribution, reducing titanium alloy stiffness and alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Recent research has demonstrated that the introduction of a gradient porous structure can effectively address the limitations of a homogeneous material structure performance [21][22][23]. This structure exhibits a porosity gradient distributed in a specific direction, enabling the targeted control of material structure to meet specific requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has demonstrated that the introduction of a gradient porous structure can effectively address the limitations of a homogeneous material structure performance [21][22][23]. This structure exhibits a porosity gradient distributed in a specific direction, enabling the targeted control of material structure to meet specific requirements.…”
Section: Introductionmentioning
confidence: 99%